Chandra X-ray spectroscopy of focused wind in the Cygnus X-1 system. II. The non-dip spectrum in the low/hard state - modulations with orbital phase - Miskovicova, Ivica; Hell, Natalie; Hanke, Manfred; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Grinberg, Victoria; Duro, Refiz; Madej, Oliwia K.; Lohfink, Anne M.; Rodriguez, Jerome; Bel, Marion Cadolle; et al. (Astronomy & Astrophysics, 2016)
Accretion onto the black hole in the system HDE 226868/Cygnus X-1 is powered by the strong line-driven stellar wind of the O-type donor star. We study the X-ray properties of the stellar wind in the hard state of Cyg X-1, as determined using data from the Chandra High Energy Transmission Gratings. Large density and temperature inhomogeneities are present in the wind, with a fraction of the wind consisting of clumps of matter with higher density and lower temperature embedded in a photoionized gas. Absorption dips observed in the light curve are believed to be caused by these clumps. This work concentrates on the non-dip spectra as a function of orbital phase. The spectra show lines of H-like and He-like ions of S, Si, Na, Mg, Al, and highly ionized Fe (Fe xvii-Fe xxiv). We measure velocity shifts, column densities, and thermal broadening of the line series. The excellent quality of these five observations allows us to investigate the orbital phase-dependence of these parameters. We show that the absorber is located close to the black hole. Doppler shifted lines point at a complex wind structure in this region, while emission lines seen in some observations are from a denser medium than the absorber. The observed line profiles are phase-dependent. Their shapes vary from pure, symmetric absorption at the superior conjunction to P Cygni profiles at the inferior conjunction of the black hole.
Keywords: Accretion; accretion disks; Stars: individual: Cyg X-1; Stars: individual: HDE 226868; Stars: winds; outflows; X-rays: binaries

Revealing the broad iron Kα line in Cygnus X-1 through simultaneous XMM-Newton, RXTE, and INTEGRAL observations - Duro, Refiz; Dauser, Thomas; Grinberg, Victoria; Miskovicova, Ivica; Rodriguez, Jerome; Tomsick, John; Hanke, Manfred; Pottschmidt, Katja; Nowak, Michael A.; Kreykenbohm, Sonja Sophie; Bel, Marion Cadolle; Bodaghee, Arash; et al. (Astronomy & Astrophysics, 2016)
We report on the analysis of the broad Fe Kα line feature of Cyg X-1 in the spectra of four simultaneous hard intermediate state observations made with the X-ray Multiple Mirror mission (XMM-Newton), the Rossi X-ray Timing Explorer (RXTE), and the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The high quality of the XMM-Newton data taken in the Modified Timing Mode of the EPIC-pn camera provides a great opportunity to investigate the broadened Fe Kα reflection line at 6.4 keV with a very high signal to noise ratio. The 4-500 keV energy range is used to constrain the underlying continuum and the reflection at higher energies. We first investigate the data by applying a phenomenological model that consists of the sum of an exponentially cutoff power law and relativistically smeared reflection. Additionally, we apply a more physical approach and model the irradiation of the accretion disk directly from the lamp post geometry. All four observations show consistent values for the black hole parameters with a spin of a 0.9, in agreement with recent measurements from reflection and disk continuum fitting. The inclination is found to be i 30°, consistent with the orbital inclination and different from inclination measurements made during the soft state, which show a higher inclination. We speculate that the difference between the inclination measurements is due to changes in the inner region of the accretion disk.
Keywords: black hole physics; gravitation; X-rays: binaries

The broad iron K alpha line of Cygnus X-1 as seen by XMM-Newton in the EPIC-pn modified timing mode - Duro, Refiz; Dauser, Thomas; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Fritz, S.; Kendziorra, E.; Kirsch, M. G. F.; Reynolds, C. S.; Staubert, R. (Astronomy & Astrophysics, 2011)
We present the analysis of the broadened, flourescent iron K alpha line in simultaneous XMM-Newton and RXTE data from the black hole Cygnus X-1. The XMM-Newton data were taken in a modified version of the timing mode of the EPIC-pn camera. In this mode the lower energy threshold of the instrument is increased to 2.8 keV to avoid telemetry drop outs due to the brightness of the source, while at the same time preserving the signal-to-noise ratio in the FeK alpha band. We find that the best-fit spectrum consists of the sum of an exponentially cutoff power-law and relativistically smeared, ionized reflection. The shape of the broadened FeKa feature is due to strong Compton broadening combined with relativistic broadening. Assuming a standard, thin accretion disk, the black hole is close to rotating maximally.
Keywords: X-rays: binaries; black hole physics; gravitation